PERFORMANCE OF MSME IN PROMOTING SOCIO-ECONOMIC DEVELOPMENT IN RURAL SECTOR OF ODISHA - Nanda, Sudhansu Sekhar; Mohapatra, Barada Prasanna; Mishra, Siddhant; Dash, Sagarika (International Journal of Psychosocial Rehabilitation, 2020)
In a developing country like India, Small Scale industries play a significant role in economic development of the country. These industries represent a stage in economic transition from traditional to modern technology after globalization. The variation in transitional nature of this process is reflected in the diversity of these industries. Most of the small scale industries use simple skills and machinery. Small scale industries also play social and political role in local employment creation, balanced resource utilization, income generation and in helping to promote change in a gradual and peaceful manner. It is focused that the smaller SSIs are growing not only numerically but also in terms of employments, investment and output. The present study is basically based on secondary data collected from unpublished journals, literature, economic survey, MSMEs annual reports and reports of government of Odisha. The research tools like ratio, percentages, average etc., are being used to reach valid findings and conclusion.